Agency of Men and Women in Marriage from the Perspective of Islamic Jurisprudence and Law (Salam International Academic Journal, 2024)
This study, titled (Agency of Men and Women in Marriage from the Perspective of Hanafi Jurisprudence and National Laws), explore the concept of agency and its rulings in the context of marriage. Agency (wakalah) in matters of personal status is a form of voluntary representation that is well established in Islamic texts (the Holy Quran and the Sunnah of the Prophet, peace be upon him) as well as the scholarly consensus. Representation is divided into various forms, one of which is agency in personal status matters. Agency is a contract through which the client (Muwakkil) authorizes another person to act legally on his/her behalf in specific and define matters. In the contemporary legal contexts, an agent is someone who handles the affairs of the principal and ensures the protection of his/her rights. This contract creates a mutual legal interdependence between the principal and the agent, allowing each party to act within their respective legal rights. In this contract, the person granting authority is referred to as the principal or client, while the person receiving the authority is called the agent (wakil). According to the majority view, the pillars of agency include the principal (Muwakkil), the agent (wakil), the subject of the agency, and the contractual wording. Recognized as legitimate and lawful in both Islamic law and the statutory laws of Afghanistan, agency outlines specific rights, obligations, and conditions for the contracting parties. An agent cannot act beyond the scope of their authority, and agency is not a permanent contract; it is contingent on specific conditions and situations. It can be terminated by the dismissal of the agent by the principal, the fulfillment of the purpose of the agency, the expiration of a specified period, the death of the principal, or the loss of legal capacity by either the agent or the principal. The importance of this research lies in the fact that Islamic laws regarding agency provide clear theories that offer reasonable and unbiased solutions for resolving legal issues in various circumstances. This research aims to clarify the rulings and laws related to agency in marriage for both men and women, based on a comparative study of Hanafi jurisprudence and national laws. This study has been conducted using library research methods and concludes with findings and a bibliography.
Keywords: Marriage; Agency; Shariah; Law; Personal Status